Himpunan dasar hukum pengangkatan anak - Soimin, Soedharyo, 1946- (Jakarta : Sinar Grafika, 2000)
Collection of regulations, ministerial decree, and court's decisions on child adoption in Indonesia.
Keywords: Adoption -- Law and legislation -- Indonesia; Adoption -- Law and legislation -- Indonesia -- Cases